Tutor assessment of medical students in problem-based learning sessions - Bader Khawaji; Emad Masuadi; Abdulrahman Alraddadi; Muhammad Anwar Khan; Syed Sameer Aga; Hatim Al-Jifree; Mohi Eldin Magzoub (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: Problem-based learning (PBL) is a method of learning that has been adopted in different curricula of different disciplines for more than 30 years; the assessment of the students in PBL sessions in medical schools is fundamental to ensure students' attainment of the expected outcomes of conducting PBL sessions and in providing the students with the feedback that help them to develop and encourage their learning. This study investigated the inter-rater reliability of the tutor assessment in assessing medical students' performance in their PBL tutorial sessions. MATERIALS AND METHODS: This study was conducted in the College of Medicine (COM), in the academic year 2021-2022. The study involved ten raters (tutors) of two genders who assessed 33 students in three separate PBL tutorial sessions. The PBL sessions were prerecorded and shown to the 10 raters for their assessment of PBL sessions. RESULTS: This study showed that male raters gave higher scores to students compared with female raters. In addition, this investigation showed low inter-rater reliability and poor agreement among the raters in assessing students' performance in PBL tutorial sessions. CONCLUSION: This study suggests that PBL tutor assessment should be reviewed and evaluated; this should be performed with consideration of using assessment domains and criteria of performance. Thus, we recommend that 360-degree assessment including tutor, self, and peer assessment should be used to provide effective feedback to students in PBL tutorial sessions.